Literature Study: Analysis of Implementation Children Learning in Science Learning Model in Elementary Schools - Sumadi, Conny Dian (Universitas Trunojoyo Madura, 2024)
This research aim to examine the literature on the analysis of the Implementation of the Children Learning in Science (CLIS) Learning Model in Elementary Schools. The data source used is research that has been published in scientific journals in Indonesia. The technique used is the purposive sampling technique via Google Scholar. This literature study was obtained from research articles from 2019-2024. The reference article focuses on the Children Learning in Science (CLIS) model in elementary schools. The method used in this study is a literature study by identifying, screening and eligibility for 8 articles were selected that were relevant to the aims and problems raised by the author. It can be concluded that the implementation of Children Learning in Science (CLIS) gives good results in learning especially in Science matters. The results are not only for the learning outcome but also in learning activities, science process skill.